Scientometric Analysis on Islamic Microfinance - Muhammad Syafii (Journal of Islamic Economics Literatures, 2020)
Islamic microfinance means a program that provides small loans to underprivileged people to undertake entrepreneurial projects that generate income to meet their personal needs based on shariah principle.Recently, Islamic microfinance has become an important research point, especially in developing countries. This study aims to determine the development of Islamic microfinance research trends published by leading journals on Islamic economics and finance. The data analyzed consisted of 208 indexed research publications. The data is then processed and analyzed using the VoS viewer application to determine the bibliometric map of the development of Islamic microfinance research. The topic trends in the last period are sharia, micro, finance, social, evidence, institutions, and factors, where the topic of finance is the most widely used in the 2019 period.